Discrete element simulation studies of angles of repose and shear flow of wet, flexible fibers. Issue 15 (3rd April 2018) - Guo, Y.; Wassgren, C.; Ketterhagen, W.; Hancock, B.; Curtis, J.
Abstract : The mechanics of wet and flexible fiber flows is better understood by analyzing agglomeration and solid phase stresses. Abstract : A discrete element method (DEM) model is developed to simulate the dynamics of wet, flexible fibers. The angles of repose of dry and wet fibers are simulated, and the simulation results are in good agreement with experimental results, validating the wet, flexible fiber model. To study wet fiber flow behavior, the model is used to simulate shear flows of wet fibers in a periodic domain under Lees–Edwards boundary conditions. Significant agglomeration is observed in dilute shear flows of wet fibers. The size of the largest agglomerate in the flow is found to depend on a Bond number, which is proportional to liquid surface tension and inversely proportional to the square of the shear strain rate. This Bond number reflects the relative importance of the liquid-bridge force to the particle's inertial force, with a larger Bond number leading to a larger agglomerate. As the fiber aspect ratio (AR) increases, the size of the largest agglomerate increases, while the coordination number in the largest agglomerate initially decreases and then increases when the AR is greater than four. A larger agglomerate with a larger coordination number is more likely to form for more flexible fibers with a smaller bond elastic modulus due to better connectivity between the more flexible fibers. Liquid viscous force resists pulling of liquid bridges and separation of contacting fibers, and therefore it facilitates larger agglomerate formation. The effect of liquid viscous force is more significant at larger shear strain rates. The solid-phase shear stress is increased due to the presence of liquid bridges in moderately dense flows. As the solid volume fraction increases, the effect of fiber–fiber friction coefficient increases sharply. When the solid volume fraction approaches the maximum packing density, the fiber–fiber friction coefficient can be a more dominant factor than the liquid bridge force in determining the solid-phase shear stress.